PENGGUNAAN PENDEKATAN BUDAYA LOKAL UNTUK MENINGKATKAN MOTIVASI BELAJAR IPA DI SEKOLAH DASAR - Fitriawanti Fitriawanti (FKIP Universitas Cenderawasih, 2023)
This paper aims to increase studentsâ€™ learning motivation in learning science with a local cultural approach. In the development of science learning in elementary schools there are many things that teachers must pay attention to, one of which is the learning approach. The local culture-based learning approach is the creation of a learning environment and the design of learning experiences that integrate local culture as part of the learning process. Culture is integrated as a tool for the learning process to motivate students to apply their knowledge. The cultural background that is owned by students and brought into the classroom during the learning process plays an important role in increasing learning motivation and the process of mastering the subject matter.Â Keywords:Â Local Cultural Approach, Learning Motivation, Science Learning